Teachers' Attitudes toward the Implementation of Student Active Learning Approach in Teaching Learning Activities - Mas'ud Yusuf (Universitas Negeri Malang, 2016)
The objective of this study was to obtain an empirical evidence concerning the attitudes of teachers of elementary schools in Pekalongan Sub District, East Lampung District toward the implementation of the student active learning (CBSA) approach in teaching-learning activities. The data were collected through questionnaire and observation, and were analyzed by t-test. The results indicated that there were significant differences in attitudes between young teachers and old ones, between teachers with a bachelor's degree and those without the degree, and between teachers with less teaching experience and those with more teaching experience. Additionally, there were no significant differences in teachers' attitudes in terms of sex and training experience